EVALUATION OF HEAT STABLE PROTEINS ABLE PROTEINS, TOTAL SOLUBLE PROTEINS AND ANTIBACTERIAL PROPERTIES OF TIES OF TIES OF COSTUS PICTUS D. DON - A. C. MANJULA; SHUBHA (The Bioscan, 2010)
Costus pictus D. Don or Costus mexicanus belongs to family costaceae. People of Karnataka and Kerala use the leaves of this plant to treat diabetes. It has hypoglycemic and antihelmenthic properties and the plant are rich in antioxidants. Heat stable proteins and total soluble proteins analysis revealed high HSP and TSP content on the leaves.Antimicrobial activity of the plant was evaluated against human pathogenic bacteria viz., Escherichia coli, Pseudomonas, Bacillus subtilis and Staphylococcus aureus. The HSP of the leaves of the plant used for the study revealed significant growth inhibitory effects. The results showed that the minimum inhibitory concentration of the leaf protein extract against Staphylococcus aureus and Pseudomonas was at 50µL/mL.MIC of Bacillus subtilis and Escherchia coli was at 75µL/mL.